PERAN GURU DALAM INTERNALISASI NILAI-NILAI AGAMA ISLAM UNTUK MEMBENTUK KARAKTER PESERTA DIDIK DI MIN 1 KOTA MALANG - M. Kasyful Haqqiridho (VICRATINA, 2019)
This study aims to determine the role of teachers in planning, implementing and evaluating the internalization of Islamic values in shaping the character of students in MIN 1 Malang City. This thesis research approach uses a qualitative descriptive approach, namely non hypothesis research. The results of the study indicate that the role of the teacher in internalizing the values of Islam in shaping the character of students in MIN 1 Malang City consists of planning, implementation and evaluation. Planning means that the teacher plans the values to be implanted which refer to the school's vision and mission. After the program was created, a team was formed which consisted of teachers as coordinators and members to focus on the internalization task. Implementation means implementing a plan that has been prepared by a designated team. Implementation in the form of assistance and supervision carried out professionally by recording the results of observations recorded in the format agreed upon previously. Evaluation means that the teacher evaluates the program that has been carried out which includes evaluating worship, attitude evaluation and evaluating results.